THE INFLUENCE OF EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE FOR MAHAKAM LANTERN GARDEN VISITORS - Lorine Kalista Noor; Rahmawati Rahmawati; Yohanes Kuleh (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to determine the effect of Experiential Marketing on Customer Loyalty (Study in Mahakam Lantern Garden Customers). The existence of tourism activities has a very big impact, one of which is reducing unemployment and increasing the standard of living of the surrounding community. The population in this study were visitors to Mahakam Lampion Garden, the sample in this study were 100 visitors. Methods of data collection are carried out by distributing questionnaires or questionnaires to respondents who become the research sample. This study used data analysis tools, namely the validity and reliability tests, so this study used the partial least square (PLS) analysis method. The tools used in data processing using the PLS Smart program. The results showed that 1) Experiential marketing had a significant effect on Mahakan Lantern Garden customer loyalty, 2) Experiential Marketing and Customer Satisfaction had a significant effect on Mahakan Lantern Garden Customer Loyalty, Keywords: Experiential Marketing, Customer Loyalty, Customer Satisfaction.